"Brothers in arms": Activity‐related skeletal changes observed on the humerus of individuals buried with and without weapons from the 10th‐century CE Carpathian Basin. (13th August 2020) - Tihanyi, Balázs; Berthon, William; Kis, Luca; Váradi, Orsolya Anna; Dutour, Olivier; Révész, László; Pálfi, György
Abstract: Investigation of warfare‐related lifestyle based on the activity‐induced skeletal changes is of great interest for bioarchaeologists. Numerous studies have described various skeletal traces connected to the regular practice of different types of weapons. However, methodological problems, such as the multifactorial aetiology of these presumed activity‐related skeletal changes, make it difficult to evaluate which changes are reliable in the identification and characterisation of a given class of individuals in a population. This paper aims to find significant morphological and metric differences on the humerus between individuals buried with and without weapons. We focused on the Hungarian Conquest period (10th‐century CE) collection of Sárrétudvari‐Hízóföld, characterised by a high number of burials associated with weapons and, especially, archery‐related equipment. Only adult males were selected for this study to decrease the influence of nonmechanical factors, such as age and sex. We analysed the bones for the presence of entheseal changes, joint changes, morphological variants, and traumas. The selection of these markers relied on anatomical and sport traumatological data. We also calculated indices of robusticity and shape based on the external measurements of the humerus. The values were compared according to the presence (armed group) or absence (unarmed group) of weapon deposits in the graves. An independent group of nonwarriors from the documented Luís Lopes Skeletal Collection (Lisbon) was also used for comparison. In general, the armed group exhibited higher rates of changes, and statistical tests revealed significant intergroup differences concerning certain entheseal changes and indices of robusticity and shape. Although the multifactorial aetiology of skeletal changes highly limits the possible interpretations, our results suggest that a set of morphological and metric features on the humerus is indicative of the practice of activities including archery and other fighting techniques. We assess that the further analysis of activity‐related changes of the upper limb bones will contribute to the recognition of the presence of warriors at a populational level.